A Resource Allocation Model for Tiger Habitat Protection - Dasgupta, Susmita; Hammer, Dan; Kraft, Robin; Wheeler, David (World Bank, Washington, DC, 2013)
Habitat conservation is critical to the survival of endangered tigers. This paper develops a resource-allocation model for the protection of tiger habitats, using information on threats to particular tiger subspecies, the quality of remaining habitat areas, the observed effectiveness of habitat protection by country, and the potential costs of protection projects i